2020
DOI: 10.1021/acssuschemeng.0c02063
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and DFT Insights on Microflower g-C3N4/BiVO4 Photocatalyst for Enhanced Photoelectrochemical Hydrogen Generation from Lake Water

Abstract: Herein, an experimental and density functional theory (DFT) analysis of the composite g-C 3 N 4 /BiVO 4 microflower photocatalysts are comprehensively discussed. A remarkable photoelectrocatalytic solar hydrogen production has been observed for the as-developed photocatalysts, with different loading amounts of g-C 3 N 4 (0.1, 0.4, 0.8, and 1.2 wt %), using lake water without the addition of sacrificial reagents. The 0.8 wt % g-C 3 N 4 /BiVO 4 microflower photocatalyst evinced remarkable photoelectrocatalytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Many effective strategies have been developed in this direction, such as constructing heterojunctions and hybridizing carbon nitride with different structure. [ 30,31 ] Lu and co‐workers introduced BiOBr with oxygen vacancies into carbon nitride. [ 32 ] The oxygen vacancies in BiOBr can trap electrons and effectively reduce electron–hole recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Many effective strategies have been developed in this direction, such as constructing heterojunctions and hybridizing carbon nitride with different structure. [ 30,31 ] Lu and co‐workers introduced BiOBr with oxygen vacancies into carbon nitride. [ 32 ] The oxygen vacancies in BiOBr can trap electrons and effectively reduce electron–hole recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the pure BiVO4 and g-C3N4 were individually prepared via a modified hydrothermal method and thermal polycondensation of urea, respectively. The details of these synthesizing protocols can be found 6 elsewhere [7]. Meanwhile, the RGO was synthesized using a modified Hummer's method reported by Samsudin et al [17] and GQDs were prepared according to the previously reported literature [20].…”
Section: Preparation Of Photocatalyst Samplementioning
confidence: 99%
“…Meanwhile, the tetragonal structure was made up of only O 2p orbitals, consequently, lengthen the transition of the photocharge carrier which can promote the recombination rate and limits the photocatalytic performance. Nevertheless, there are several bottleneck issues of the pure BiVO4 which has hindered the overall practicality of this semiconductor material [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[ 65 ] The charge distribution in WS 2 is uniform, which is attributed to the high spatial symmetry of its 2D nanosheets structure, and the charge is difficult to transfer between layers because of the van der Waals forces inhibit further transfer of photoelectric charges. In contrast, due to the doping of Co 2+ on the (100) crystal plane of WS 2 that the defective energy level is generated and promoted the secondary migration of charge to Co 2+ , the charge density in the (100) crystal plane of Co–WS 2 has significant change, which manifests that the reduction process occur on the interface of Co–WS 2 , [ 66 ] respectively. This shows that after the element doping, the intrinsic symmetry structure of the WS 2 2D material was broken, and the surface is formed an electron transfer channel.…”
Section: Resultsmentioning
confidence: 99%